Barriers to successful climate change policy implementation in Uganda - Okolo, Wendy; Twyman, Jennifer; Ampaire, Edidah L.; Acosta, M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
A multi-level analysis has examined how policy processes within agriculture, forestry, natural resource- and land management in Uganda support or undermine climate change adaptive responses and policy implementation with a particular focus on the Nwoya and Rakai districts. This Info Note summarizes the findings.